Penguatan Pemahaman Bahaya Pernikahan Dini Melalui Intervensi Literasi Kepada Santriwati Pondok Pesantren Miftahul Hasan Pakusari Jember: Strengthening Understanding of the Dangers of Early Marriage Through Literacy Interventions for Female Students at the Miftahul Hasan Pakusari Jember Islamic Boarding School - Turmudi, Imam; Yusuf, David Ilham (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Early marriage is considered a shortcut to escape from economic hardship. When parents cannot afford their children's school tuition, they will marry them instead. However, in many cases, early brides and grooms have not gained sufficient understanding of the functions of marriage and the respective roles they need to play. Based on these, this community service sought to reshape society's understanding by reinforcing marriage literacy, especially among female students at Miftahul Hasan Islamic Boarding School in Pakusari-Jember. The setting was deliberately chosen because most of the female students there have already become engaged. The Asset-Based Community Development (ABCD) community service approach was implemented. The procedure began with several observations of the community service respondents, followed by reinforcement of marriage literacy. Lastly, the evaluation was used to elicit reflections. The findings showed several improvements; first, their understanding of the dynamics of a marriage has improved; second, their understanding of personal readiness, such as reproductive readiness, economic readiness, children's caregiving, and household conflict management; third, their understanding of the function of a marriage and their respective roles as a husband and a wife.